2018
DOI: 10.1177/1103308818757037
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Party Preference in Adolescence and Early Adulthood: How and When Does It Occur in the Multiparty Context of the Netherlands?

Abstract: This cohort-sequential panel study on Dutch youths (N = 3394) and their parents examined the formation of party preference between age 12 and 25. Specifically, it aimed to pinpoint the most formative component and age in a multiparty context. Opinionation, stability and correlates were examined for three components of party preference: party identification, voting intention and left-right identification. Results revealed that most youths formed a preference at some point during their early life. The 6-year sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…Their presence is consistent with the observation that left-right is the primary long-term determinant of voting behaviour in many West-European countries (e.g., Van der Eijk & Franklin, 1996;Tillie & Fennema, 1998) and that most voters vote for either a leftist or a rightist party in subsequent elections (Van der Meer et al, 2015). More generally, the structuring and stabilizing effect of ideological blocks of parties that was observed in our analysis is consistent with the observation that left-right orientation is the main driving force behind early adolescent formation, intergenerational transmission, and life-course stability of party preferences in countries like the Netherlands (Percheron & Jennings, 1981;Rico & Jennings, 2015;Rekker et al, 2018). Interestingly, the analyses also revealed that ideological camps can be used to detect how some parties fall outside the regular pattern of electoral competition.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Their presence is consistent with the observation that left-right is the primary long-term determinant of voting behaviour in many West-European countries (e.g., Van der Eijk & Franklin, 1996;Tillie & Fennema, 1998) and that most voters vote for either a leftist or a rightist party in subsequent elections (Van der Meer et al, 2015). More generally, the structuring and stabilizing effect of ideological blocks of parties that was observed in our analysis is consistent with the observation that left-right orientation is the main driving force behind early adolescent formation, intergenerational transmission, and life-course stability of party preferences in countries like the Netherlands (Percheron & Jennings, 1981;Rico & Jennings, 2015;Rekker et al, 2018). Interestingly, the analyses also revealed that ideological camps can be used to detect how some parties fall outside the regular pattern of electoral competition.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, a study among Dutch voters showed that the stability across six years was rather strong for attitudes towards redistribution, a symbol of the socio-economic left-right dimension, as well as for attitudes towards multiculturalism, a symbol of the cultural dimension (over-time correlation coefficients equalled 0.57 and 0.69, respectively; Rekker et al, 2015). Left-right selfclassification in the same period was also rather stable, as only one out of ten voters moved from the left to the right or vice versa (over-time correlation coefficient equalled 0.59 ;Rekker et al, 2018). Likewise, an American study found strong stability across a 17-year period for party identification (over-time correlation coefficient equalled 0.72; Sears & Funk, 1999).…”
Section: The Stability Of Voters' Consideration Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…While scholars disagree, for the development of political orientations, the formative years are roughly between 12 and 25. The strongest learning effects take place around the age of 18 (Bartels and Jackman 2014;Rekker et al 2019;Schuman and Rodgers 2004).…”
Section: Political Socialization Cohort and Age Effectsmentioning
confidence: 99%
“…Rico and Jennings, 2016). Rekker et al (2019) found that, although young people develop their own social status as well as an educational and professional career after the formative age of 18, the parents' influence remains. In fact, most young people are said to build on their parents' attitudes, often taking on a more extreme stance (Slootman and Tillie, 2006).…”
Section: Fundingmentioning
confidence: 99%